Scientific production on dental caries 2014–2018: a bibliometric study in Web of Science - Jaimes-Monroy, Gustavo; Valderrama-Salgado, Ángela Ivonne; Prieto-Cárdenas, Elver Steven; Rincón-Bermúdez, Claudia Milena (Revista Facultad de Odontología Universidad de Antioquia, 2019)
Introduction: the aim was to conduct a bibliometric study regarding the scientific production on dental caries in the period 2014–2018. Methods: a bibliometric study in a five-year period including 2,291 publications from the Web of Science database. The following variables were included: annual production of articles, journals, authors, cooperation, and citation analysis. Results: a sustained production of information has been conducted throughout the study years. Paiva, from Brazil, is the author with the largest number of publications (n = 33); the journal with the highest number of articles is Caries Research (n = 176). The United States and Brazil are the countries with the most publications on this topic. Conclusions: there is a sustained production of publications on dental caries, validating this topic and showing the importance of scientific groups conducting research in the fields of diagnosis, prevention, and public health mainly.